Growth trait genetic parameters in a progeny trial of Pinus oocarpa - Fabián-Plesníková, Irenka; Sáenz-Romero, Cuauhtémoc; Cruz de León, José; Martínez-Trujillo, Miguel; Sánchez Vargas, Nahum M. (Instituto de Ecología, A.C., 2020)
In Mexico, Pinus oocarpa Schiede ex Schltdl is one of the forest tree species of major ecological (for its wide geographical distribution), and economic importance (for the resin extraction in natural stands). More intensive exploitation will require establishing commercial plantations, which could be multipurpose: for resin tapping and wood. The present study aimed to explore the genetic control (heritability) of the growth characteristics for total height (HGT), stem base diameter (DIAM), diameter at breast height (DBH) of half-sib progenies from trees originally selected for its resin yield. All these in order to assess the feasibility of a multipurpose breeding program. In 2011, it was established a progeny trial in Michoacán, Mexico, with 27 open-pollinated half-sib families in an experimental design of 10 randomized complete blocks. Five years after its establishment, the mean values were HGT = 5.5 m, in DIAM of 13.4 cm, and DBH = 10.4 cm. We found statistically significant differences among families for all the characteristics. Narrow-sense heritability at individual level (h2i) was: HGT = 0.15, DIAM = 0.22, and DBH = 0.17; at family mean level (h2f) it was 0.44, 0.54, and 0.47, respectively. At an intensity of selection of the best individuals of i = 1.4, the genetic gains for HGT, DIAM, and DBH were 3.9, 5.2, and 5.0%, respectively. If, in the future, it is demonstrated that there is an association between diameter and resin yield, it would be feasible to increase both traits through the selection of the best individuals with the greatest diameters.